Risk factors and longevity - E. D. Golovanova; P. A. Iliyushchenkov; S. V. Aleksashkin; A. V. Shpakov (Кардиоваскулярная терапия и профилактика, 2016)
Aim. To study the specifics of prevalence dispersion of various riskfactors (RF) of cardiovascular diseases (CVD) among centenarians of Smolenskaya Region.Material and methods. Totally questioned 112 person of male (n=58) and female (n=54) gender a the age ≥90 y. o., hospitalized in Smolenskiy Regional clinical hospital for Military veterans, during 2013-2015 y. Questionnaire included the following modules: personal data, anthropometric values, module for bad habits, family history, clinical and laboratory study. All patients were undergoing daily blood pressure (BP) measurements. Criteria for arterial hypertension (AH) was BP >140/90 mmHg and regular antihypertension medication therapy. All patients also underwent serum tests of total cholesterol, triglycerides, glucose, fibrinogen, C-reactive protein, total bilirubin, creatinine, urea (analyser STAT FAX “USA”). In 30 centenarians, also the vascular stiffness was studied of the muscular-elastic vessels by pulse wave velocity method.Results. The low rate of smoking (2,7%) and alcohol consumption (16,9%) is found, as the development of AH in later ontogenesis with more prominent involvement of peripheral arteries of lower extremities. For the centenarians of Smolenskiy Region it is specific to demonstrate such positive psychosocial factors as higher educational level and selfcare abilities remaining. 34,6-41,9% of persons included, reported relatives-centenarians of 1st grade of consanguinity. Most of participants (64,2%) had enough physical activity and did not show dyslipidaemia or metabolic disorders.Conclusion. Connection of the minimum CVD RF with good heredity and psychosocial attitudes towards self-development and education potentiates the achievement of an active longevity.